ANALYSIS OF MEASURES ITEMS IN DEVELOPMENT OF INSTRUMENTS SELF-ASSESSMENT (RASCH MODELING APPLICATION) - lailiyah lailiyah; Yetti Supriyati; Komarudin Komarudin (lppm Universitas Negeri Jakarta, 2018)
This analysis aims to determine the quality of the instrument items that have been developed in the empirical test phase one. Tests were carried out on 46 items to 219 respondents in SMA Ksatrya Jakarta. The item quality is seen from the fit or not fit and the level of difficulty of the item that has been developed. The fit or unfit criteria are seen in INFIT and OUTFIT, both MNSQ and ZSTD, and Pt-Measure Correlation values. The level of difficulty of the item is seen in the entry number column which is indicated by the magnitude of the logit value and has been sorted from the hardest to the easiest. Based on the results of analysis with the help of software winstep obtained 39 items statement fit with the model and the number of respondents 194, the three criteria above (MNSQ, ZSTD, and Pt.Measure Correlation) has been met. This means that 39 items are valid. The result of the analysis also shows the most difficult item sequence is item 5 with logit value 63,32, and the easiest item is item 44 with logit value 36,13. The resulting fit instrument must have gone through several stages of analysis. When there are items that are not fit, the item is issued, as well as the respondent. So that obtained a set of measuring instruments that are valid / fit with the model and can be used for the purposes of assessment.     Keyword: self-assessment, infit, outfit, ZSTD, and Rasch Model.